MP32: Mid-morning huddle: a coordinated team approach to facilitating disposition of older adults. (May 2019) - Kelly, N.; Campbell, S.
Abstract : Background : Older adults in the emergency department (ED) take an increasingly larger portion of resources, have increased length of stay and a higher likelihood of adverse outcomes. In many cases bad planning, multiple vague handovers, and lack of coordinated care exacerbate this problem. With the impending onset of our aging population this is a situation that can be expected to compound in complexity in the years to come.Aim Statement: We describe daily interdisciplinary review of ED patients over the age of 75 years (or otherwise identified as a challenging discharge) to discuss barriers and facilitators to discharge/disposition. We will use data to identify the impact of this particular population to ED flow.Measures & Design : This initiative developed from our participation in the Acute Care of the Elderly (ACE) Collaborative and applies Plan/Do/Study/Act (PDSA) cycles and run reports to compare: length of stay; Identification of Seniors at Risk (ISAR) screening tool; ED census, admission/discharge rates, bounce back rates, consulting services, and interdisciplinary participation.Evaluation/Results: The average daily census of our ED between the months of July-October of 2018 was over 211 patients/day, of which over 12% were patients 75 years and older. We conducted over 70 huddles, reviewing an average of 11 patients per day. The average length of stay for patients at the time of the huddle was 19 hours, significantly higher than the general emergency population. Next day admission and discharge rates were comparable, 44.8% and 43.1% respectively with the additional patients remaining in the ED with no disposition. Internal medicine was consulted on 30% of all huddle patients and 38.4% subsequently admitted. Thirty day bounce back rates for huddle patients discharged home was 29.3%. Around 60% of patients 75 and older were screened with the ISAR and 55.7% of these were positive (2 or more questions).Discussion/Impact: Older patients consume a disproportionate amount of ED resources. Daily interdisciplinary 'geriatric huddles' improved communication between members of the ED team and with consulting services. The huddles enhanced awareness of the unique demands that older adults place on the flow of the ED, and identified opportunities to enhance patient flow.